Preparation and In-vitro Characterization of Giant Superparamagnetic Nanobeads: A Proof of Concept - Amirreza Fatemi; Mohammad Javad Raee; Ali Mohammad Tamaddon; Sara Sadeghian; Salmeh Amiri; Dena Firouzabadi; Fakhrossadat Farvadi (Trends in Pharmaceutical Sciences)
The isolation of biomolecules from complex biological environments is a crucial step in the accurate analysis of biomarkers, which in turn is vital for enhancing the precision of medical diagnoses. Among the various techniques employed for biomarker separation, immunomagnetic separation utilizing superparamagnetic iron oxide nanoparticles (SPIONs) has emerged as a promising approach. Nonetheless, the diminutive size of SPIONs poses challenges regarding their robustness, particularly in the efficient extraction of macromolecules from diverse biological samples. This study addresses this pressing concern by investigating methods to enhance the magnetic properties of these nanoparticles. Specifically, we focus on increasing the magnetic unit size while preserving their superparamagnetic characteristics. Through a novel methodological approach, we successfully created giant superparamagnetic nanoclusters via click binding of biotinylated SPIONs with avidin macromolecules. These large nanoclusters exhibited favorable magnetic properties, indicating their potential for significant application in biomarker discovery and analysis, thus paving the way for advancements in biomedical diagnostics.